Association of Physical Activity in Childhood and Early Adulthood With Carotid Artery Elasticity 21 Years Later: The Cardiovascular Risk in Young Finns Study - Pälve, Kristiina S. (Blackwell Publishing Ltd, 2014)
BACKGROUND: Decreased arterial elasticity is a risk factor for several cardiovascular outcomes. Longitudinal data on the effect of physical activity in youth on adult arterial elasticity are limited. The aim of this study was to determine the long‐term effects of physical activity in children and young adults on carotid artery elasticity after 21 years of follow‐up. METHODS AND RESULTS: Participants were 1417 children (aged 9 to 15 years) and 999 young adults (aged 18 to 24 years) from the prospective Cardiovascular Risk in Young Finns Study. Participants had questionnaire measures of leisure‐time physical activity available from 1986 and ultrasound‐derived indices of carotid artery elasticity measured in 2007. Carotid artery elasticity indices were distensibility (%/10 mm Hg), Young's elastic modulus (kPa), and stiffness index (unitless). Physical activity at age 18 to 24 years was directly associated with distensibility (β=0.068, P=0.014) and inversely with Young's elastic modulus (β=−0.057, P=0.0037) and indirectly with stiffness index (β=−0.050, P=0.0028) 21 years later in males and females. The associations remained after adjustment for age, sex, body mass index, smoking, systolic blood pressure, serum lipids and insulin, and 21‐year change in physical activity. At age 9 to 15 years, the favorable association, remaining after adjustment, was found in males (distensibility [β=0.097, P=0.010], Young's elastic modulus [β=−0.060, P=0.028], and stiffness index [β=−0.062, P=0.007]) but not in females (P=0.70, P=0.85, and P=0.91, respectively). CONCLUSIONS: Leisure‐time physical activity in boys and young adults is associated with carotid artery elasticity later in life, suggesting that higher levels of physical activity in youth may benefit future cardiovascular health.